SYNTHESIS, COMPUTER AIDED SCREENING AND PHARMACOLOGICAL EVALUATION OF 2/3-SUBSTITUTED-6(4-METHYLPHENYL)-4,5-DIHYDROPYRIDAZIN3(2H)-ONES, AND PYRIDAZINE SUBSTITUTED TRIAZINE - Khokra, Sukhbir Lal; Seth, Sonakshi; Garg, Shama S; Kaushik, Pawan; Ahmad, Aftab; Khan, Shah Alam; Husain4, Asif (INDONESIAN JOURNAL OF PHARMACY, 2015)
The present research work involved synthesis of some new pyridazine derivatives and evaluation of their analgesic and anti-inflammatory activities in experimental animals to obtain safer non-steroidal anti-inflammatory agents (NSAIDs). Friedel-Crafts acylation reaction of succinic anhydride with toluene in the presence of anhydrous aluminum chloride gave 4-(4-methylphenyl)-4-oxo-butanoic acid (1). The aryl propionic acid 1 on reaction with phenyl hydrazine and hydrazine hydrate yielded the pyridazinone derivative 2 and 3, respectively. Reaction of the compound 3 with phosphorus oxychloride (POCl3) produced the corresponding chloropyridazine derivative 4. A 4-hydroxymethyl derivative of dihydropyridazinone (5) was synthesized by condensing 3 with methanol and formaldehyde (HCHO). The compound 5 on further treatment with guanidine hydrochloride in ethanol gave the pyridazino-triazine (6). The synthesized compounds were investigated for their analgesic activity in mice and anti-inflammatory activity in Wistar albino rats. The molecular, pharmacokinetic and toxicity properties of the synthesized compounds were calculated by Molinspiration and Osiris property explorer software. The results of in-vivo anti-inflammatory studies revealed that the compound. 4 showed maximum inhibition in paw edema volume followed by compound 3 while the compound 4 exhibited excellentÂ  peripheral analgesic activity (74%) followed by the compound 5. Compound s 4 and 5 also showed good central analgesic effect increased the reaction time to 90 minutes. All the title compounds except compound 5 are predicted to be safe by Osiris online software and are likely to have good oral bioavailability as they obey Lipinskiâs rule of five for drug likeness.Keywords:Â  Pyridazinone, Hydrazine derivatives, Chloropyridazine, Triazin-2-imine.